Native Americans of the frontier - Sundling, Charles W. (Minneapolis, MN : Abdo & Daughters, 2000)
Describes the life and customs of Native American people living on the Great Plains before the arrival of the white man.
Includes index.
Keywords: Indians of North America -- Great Plains -- History -- Juvenile literature; Indians of North America -- Great Plains -- Social life and customs -- Juvenile literature; Indians of North America -- Great Plains